Comparison of plasma levels of different species of trans fatty acids in Japanese male patients with acute coronary syndrome versus healthy men. (May 2019) - Koba, Shinji; Takao, Tetsuya; Shimizu, Fumiko; Ogawa, Mutsumi; Ishii, Yukie; Yokota, Yuuya; Furuyama, Fumiaki; Tsunoda, Fumiyoshi; Shoji, Makoto; Harris, William S.; Takada, Akikazu
Abstract: Background and aims: It remains unclear how trans fatty acid (TFA) at low-level intake affect lipid levels and the development of acute coronary syndrome (ACS). The study aimed to investigate how plasma TFA composition differs between male patients with ACS and healthy men. Methods: Plasma fatty acid (FA) composition (as determined by gas chromatography) was analyzed in ACS patients on hospital admission and compared to that of age-adjusted healthy men. Results: Total FA and TFA levels were similar between ACS and control subjects. Palmitelaidic acid, ruminant-derived TFA (R-TFA), levels were lower in ACS patients (0.17 ± 0.06 vs . 0.20 ± 0.06 of total FA, in ACS and control, respectively, p< 0.01), and were significantly directly associated with HDL cholesterol (HDL-C) (rho = 0.269) and n-3 polyunsaturated FA (n-3 PUFA) (rho = 0.442). Linoleic trans isomers (total C18:2 TFA), primary industrially-produced TFA (IP-TFAs), were significantly higher in ACS patients (0.68 ± 0.17 vs . 0.60 ± 0.20 of total FA, in ACS and control, respectively). Total trans -C18:1 isomers were comparable between ACS and control. Differences between ACS and controls in C18:1 trans varied by specific C18:1 trans species. Absolute concentrations of trans -C18:2 isomers were significantly directly associated with LDL-C and non-HDL-C in ACS men. The ACS patients showed significantly lower levels of both n-6 and n-3 PUFA (i.e., eicosapentaenoic, docosahexaenoic and arachidonic acids). Conclusions: There were several case-control differences in specific TFA that could potential affect risk for ACS. Japanese ACS patients, especially middle-aged patients, may consume less R-TFA. Graphical abstract: Image 1 Highlights: There are several differences in trans -C18:1 positional isomers between acute coronary syndrome (ACS) and control. Palmitelaidic acid, ruminant-derived TFA were lower in ACS patients, especially middle-aged patients. Linoleic trans isomers, industrially-produced TFA (IP-TFAs) were higher in ACS. IP-TFA to arachidonic acid (AA) ratio was significantly higher in ACS, especially elder ACS patients. Palmitelaidic acid was significantly directly associated with HDL-C, EPA+DHA, and EPA+DHA/AA ratios.